Choosing orthodontic correction for the genetic determination of complex rehabilitation of children with disabilities cleft lip and palate during the mixed dentition - S. S. Gushina; A. F. Verapatvelyan (Кубанский научный медицинский вестник, 2014)
Direct stimulation of the growth potential of orthodontic upper jaw during all periods of the formation of occlusion in children with unilateral cross-cutting cleft lip and palate makes it possible to restore the size and shape of the dental arches during the mixed dentition and to ensure stability of the results of complex treatment. Multi-faceted approach to the rehabilitation of children with orthodontic cleft lip and palate considering genetic determination to reduce dentoalveolar deformations due to congenital anomalies and surgical interventions.